Musculoskeletal problems in PD patients have no association with socioeconomic status. (December 2019) - Kim, Ahro; Kim, Aryun; Kim, Yoon; Kim, Young Eun; Kim, Han-Joon; Jeon, Beomseok
Highlights: Socioeconomic status had no association with musculoskeletal problems. A gender difference was shown in the risk factors of musculoskeletal problems. Women had a higher risk of musculoskeletal problems. Abstract: Musculoskeletal problems are common in the general population and also in Parkinson's disease (PD) patients. We aimed to assess whether socioeconomic status (SES) is associated with the prevalence of musculoskeletal problems in PD patients. This cross-sectional study used data a total of 309 patients with PD who were interviewed, and their medical records were reviewed from the Movement Disorder Clinic of Seoul National University Hospital from March to December 2016. The PD patients were divided into four age groups. Education level was divided into three groups: primary school, middle and high school, and college or higher. Monthly household income was divided into four groups. Occupation was divided into three groups: manual workers, non-manual workers, and others (unemployed and housewives). Patients with musculoskeletal problems were more likely to be women and older, had a more impaired Activities of Daily Living and depressive symptoms and less education, and were less likely to be engaged in non-manual work. For both genders, SES had no association with musculoskeletal problems. For men, similar to the patients overall, age had a positive association with musculoskeletal problems. The Unified Parkinson's Disease Rating Scale I & II scores also had positive associations with musculoskeletal problems. For women, Beck depression inventory and diabetes mellitus also had positive and negative associations with musculoskeletal problems, respectively. SES had no association with musculoskeletal problems in PD patients. Women had a higher risk of musculoskeletal problems. A gender difference was shown in the risk factors of musculoskeletal problems.